Isolated Breast Hydatid Cyst: A Rare Case Report (GAIMS Journal of Medical Sciences, 2026)
Echinococcosis, caused by Echinococcus granulosus, is a significant yet uncommon zoonotic disease. Humans become infected by eating food contaminated with dog feces or by coming into close contact with animals; the liver and lungs are usually affected. Nevertheless, breast hydatid cysts are extremely uncommon, making for only 0.27% of all occurrences. This report describes the case of a 37-year-old woman who had been experiencing pain and swelling in her right breast for six months.